Host Disease Tolerance Predicts Transmission Probability for a Songbird Pathogen - Amberleigh E. Henschen; Francis E. Tillman; Sarah Coleman Ruston; Dana M. Hawley; James S. Adelman (Ecology and Evolution)
ABSTRACT Disease tolerance reduces the per‐pathogen fitness costs of infection for hosts and is an important component of host adaptation to pathogens. However, how disease tolerance affects host transmission potential is not well understood, especially because there are many potential mechanisms that facilitate host tolerance. For example, tissue‐specific host tolerance leads to the reduction of host pathology, regardless of pathogen load. Hosts may also exhibit behavioral tolerance, where normal behaviors are maintained even while harboring high pathogen loads. Here, we examined the impacts that tissue‐specific and behavioral tolerance have on transmission in house finches (Haemorhous mexicanus) infected with a common and highly transmissible bacterial pathogen, Mycoplasma gallisepticum (MG). MG causes conjunctivitis in house finches and severely reduces population numbers after it arrives in a new area. Wild house finch populations differ in tissue‐specific tolerance to MG and here we assessed how this variation in tolerance influences transmission success. We inoculated wild‐captured, MG‐naïve individuals from two populations that are on the extremes of tissue‐specific tolerance to MG and determined the likelihood of these “index” individuals transmitting MG to an uninfected, susceptible cagemate. Higher tissue‐specific tolerance results in reduced conjunctivitis, which is associated with decreased deposition and spread of MG. Thus, we predicted that individuals with high tissue‐specific tolerance would be less likely to transmit MG. In contrast, we predicted that behavioral tolerance would be linked to higher transmission, as more tolerant individuals spent more time on a feeder shared with a susceptible individual despite high pathogen loads. In agreement with our prediction, individuals with high tissue‐specific tolerance were less likely to transmit MG. However, there was no effect of behavioral tolerance on the likelihood of MG transmission. Our results highlight that it is key to consider how different mechanisms of tolerance affect transmission and, therefore, host‐pathogen coevolution and epidemic dynamics.